Implementation of financial report and taxation training: performance of MSMEs in Special Regions Yogyakarta - Siti Resmi; Reza Widhar Pahlevi; Fran Sayekti (Jurnal Siasat Bisnis, 2021)
This study aims to determine and analyze the application of financial report and taxation training for Micro, Small, and Medium Enterprises (MSMEs) as well as any constraints faced ahead. This study observed 25 MSMEs in Special Region of Yogyakarta using a convenience sampling method. The data used are primary data obtained through interviews and focus group discussions. This research used qualitative analysis techniques. The result shows that MSMEs did not keep records because it was difficult and inconvenient. It also found that MSMEs have a tax ID number (NPWP) but did not pay and report their taxes. Tax is perceived as an expense which results in a reduced profit. However, financial reports and knowledge of taxation are required when applying for bank loans and obtaining government incentive funds. With training in the preparation of financial and tax reports, MSMEs are aware of the importance of financial and tax reports. Financial reports, NPWP, and tax return (SPT) filling are factors that can improve their business performance.